Amyloid β, Tau, and α-Synuclein aggregates in the pathogenesis, prognosis, and therapeutics for neurodegenerative diseases. (July 2022) - Sengupta, Urmi; Kayed, Rakez
Abstract: Aggregation of specific proteins are histopathological hallmarks of several neurodegenerative diseases, such as, Amyloid β (Aβ) plaques and tau neurofibrillary tangles in Alzheimer's disease (AD); morphologically different inclusions of ratiometric 3 repeat (3 R) and 4 repeat (4 R) tau isoforms in progressive supranuclear palsy (PSP), corticobasal degeneration (CBD), and Pick's disease (PiD); α-Synuclein (α-Syn) containing Lewy bodies (LBs) and dystrophic Lewy neurites (LNs) in Parkinson's disease (PD) and dementia with Lewy bodies (DLB). However, mixed brain protein pathologies have been frequently observed in many of these diseases and in normal aging brains, among which Aβ/tau and tau/α-Syn crosstalks have received increased attention. Interestingly, studies have also shown synergistic interplay among Aβ, tau, and α-Syn in several neurodegenerative diseases, suggesting a protein triumvirate. In this review, we summarize the emerging evidence of Aβ, tau, and α-Syn aggregation in pathophysiology, and their overlap in a spectrum of neurodegenerative diseases including AD, PSP, PiD, CBD, PD and DLB. We discuss the prognostic advancements made in biomarker and imaging techniques in the triumvirate proteinopathies. Finally, we discuss the combined therapeutic modality involving biomarkers and imaging techniques for future combinatorial immunotherapeutic targeting more than one protein aggregates. We hope that such a multitarget therapeutic approach will have synergistic or additive effects to manage neurodegenerative diseases with two or more protein pathologies that might uncover a promising strategy for personalized combination therapies. Managing neurodegenerative diseases by optimizing the diagnostic criteria and the correct combination of immunotherapies will be a key factor in the success of future treatment. Highlights: Co-occurring proteinopathies confound disease diagnosis and treatment development. Overlapping Aβ, tau, and α-Syn pathologies are observed in AD and related diseases. Aβ, tau, and α-Syn converge directly or indirectly in in vitro and in vivo . We review recent advancements in biomarkers and neuroimaging for Aβ, tau, and α-Syn. A combined therapeutic approach might be more successful for disease intervention.